Inovasi kepala sekolah dalam mengembangkan sekolah berkemajuan di SMK Negeri 2 Surakarta - Faizal Adira Wicaksana; Nurul Latifatul Inayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Educational institutions should have an advantage that leads to positive things, for example graduates who have superior quality so that they bring results and benefits for both students and the educational institution itself. So that educational institutions have advantages or uniqueness that will later attract the attention of the wider community to trust these educational institutions. Thus, to improve the quality of education, it is necessary to familiarize with disciplinary habits. The culture in the school can be said to be good if the culture is able to make all elements in the school behave politely, be disciplined and care for others. Thus, this study aims to find and describe the principal's innovations in developing progressive schools at Surakarta 2 State Vocational School. While the driving factor is that with a large number of teachers at SMKN 2 Surakarta, most of the teachers at SMKN 2 Surakarta have become professional teachers, then the facilities and infrastructure at SMKN 2 Surakarta are more numerous and better when compared to other schools. Whereas what hinders the development of innovation is from the HR (Human Resources) side it is not easy to unite the same thoughts to the management team when making changes and innovations.